Mutans Streptococci and Lactobacilli: Colonization Patterns and Genotypic Characterization of Cariogenic Bacterial Species in American Indian Children - Villhauer, Alissa; Lynch, David; Postler, Taylor; Dawson, Deborah; Drake, David (Frontiers in Dental Medicine, 2021)
The purpose of this study was to investigate the presence of Streptococcus mutans, Streptococcus sobrinus, and Lactobacillus species in an American Indian population displaying a high incidence of severe early childhood caries (S-ECC) and to explore the genotypic diversity and fidelity of transmission of S. sobrinus in this population. Methods: We report here on the microbial profiles of 71 children compiled from birth to 36 months of age and initial exploration of genotypic diversity in a subset of 40 mother/child dyads. Whole mouth plaque samples were collected from mother/child dyads in a Northern Plains American Indian cohort. Mutans streptococci (MS) and Lactobacillus counts were recorded and presence/absence of S. mutans, S. sobrinus, and Lactobacillus was noted for each child. S. sobrinus was isolated and genotyped via arbitrarily primed-polymerase chain reaction (AP-PCR). Results: Subjects were divided into caries active (CA) and caries free (CF). S. mutans, S. sobrinus, and Lactobacillus species were detected more frequently in CA children. Distribution of MS and Lactobacillus counts was also significantly different between the two groups, as was the distribution of three species colonization profiles. Twelve S. sobrinus genotypes were detected in the subset of mother/child dyads. Individual subjects displayed a range of 0-3 distinct genotypes while mother/child pairs displayed a range of 1-5 genotypes. Eighty-three percent of children shared at least 1 genotype with his/her mother. Conclusion: Caries active children in this population display different microbial profiles than the caries free children in this cohort. A small number of S. sobrinus genotypes appear to be very common in this population. A high rate of vertical transmission of S. sobrinus from mother to child is seen in these mother/child dyads.